Synthesis and characterization of bromelain enzyme/poly (vinyl alcohol) as potential bone scaffold - Azri, Qurratul Aini; Mat Jahari, Fatini Illyana; Jahir Hussain, Fathima Shahitha; Zulkifli, Farah Hanani (Penerbit Universiti Malaysia Pahang, 2022)
3D bone scaffold is the temporary constructs substrates that enable and activate the bonding and reproduction of osteoinductive cells that lead to the creation of new usable tissues. The objectives of this research study are to synthesize and fabricate bromelain/poly (vinyl alcohol) (PVA) porous substrates by using a lyophilization technique and study the properties of the scaffold subsequently. In this study, bromelain (1, 2 and 3 wt.%) and PVA (15 wt.%) solutions were prepared, then mixed overnight to get homogeneous solution. The solutions were frozen for 24 hours before being freeze-dried under vacuum for 7 days at -80 °C. Thereafter, the porous substrates were crosslinked by using glutaraldehyde and characterized using X-ray Diffraction (XRD), Differential Scanning Calorimetry (DSC) and Fourier Transform Infrared Spectroscopy (FTIR). According to the XRD findings, PVA/bromelain scaffolds exhibits great degree of crystallinity at 21.11° and 41.05°. The FTIR results shows no significant effect on the absorption peak at varied concentration of bromelain in bromelain/PVA substrates. For the DSC result, the glass transition temperature was found in the range of 65 to 75 °C. For TGA curve, it was obvious that the temperatures of the weight loss regions gradually increased with the bromelain content, indicating that bromelain improves the stability of the bromelain/PVA membranes at high temperatures. Bromelain/PVA showed high porosity (>75%), and water-swelling ratio within 50 to 150 percent after 24, 48, and 72 hours immersion period. This newly developed scaffold composition may serve as a foundation for the growth of bone tissue.